STUDENTS’ PERCEPTION IN USING HOT POTATOES AS A MEDIA OF VOCABULARY TEST AT SMKN 2 PALANGKA RAYA - Fitriana Yana -; Bahing Bahing; Misrita Misrita (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
This research aims to investigate the students’ perception of using Hot Potatoes software as the media of vocabulary test at SMKN 2 Palangka Raya, Indonesia. It was qualitative research with five participating students as the participants from grade X OTKP 3. An in-depth semi-structured interview was applied as the data collection technique. The theme-based analysis was used in this study. The finding shows that the students give a positive response to the use of Hot Potatoes. Students’ perceptions while learning using Hot Potatoes are; first, Hot Potatoes is more practical for a vocabulary test. Second, the game can attract the students’ attention to the test. Third, it helps the students to be more motivated in the classroom. This study implies that the use of Hot Potatoes at the tenth grade students in SMKN 2 Palangka Raya can be an alternative for teachers to teach vocabulary and provide fun learning activities for the students.